2018
DOI: 10.1111/jzo.12572
|View full text |Cite
|
Sign up to set email alerts
|

Starting small: long‐term consequences in a managed large‐mammal population

Abstract: Small populations are vulnerable to founder effects, stochastic demographic events and inbreeding depression. These factors raise the extinction probability of small populations, and thus effective management plans for endangered species have become essential. The black rhinoceros (Diceros bicornis) survived a historic global population crash and is currently facing renewed threat through poaching, population fragmentation and isolation. South Africa is home to approximately 36% of the world's remaining black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Currently, fewer than 100 black rhinos (southern and eastern sub-species combined) reside in zoological institutions in North America as a reservoir against potential extinction 2 . However, the ex situ population experiences its own threats to survival, including a myriad of unusual disease syndromes not generally described in the wild 310 , as well as poor reproduction 11,12 and fragmented populations 3 . Across mammals, recent studies have suggested that microbiome differences between wild and captive populations may influence overall health in general and digestive and immune functions in particular 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, fewer than 100 black rhinos (southern and eastern sub-species combined) reside in zoological institutions in North America as a reservoir against potential extinction 2 . However, the ex situ population experiences its own threats to survival, including a myriad of unusual disease syndromes not generally described in the wild 310 , as well as poor reproduction 11,12 and fragmented populations 3 . Across mammals, recent studies have suggested that microbiome differences between wild and captive populations may influence overall health in general and digestive and immune functions in particular 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Domestication is associated with changes to an animal's natural environment, diet, breeding and behaviour, [1][2][3][4] often with a negative impact on animal health. [5][6][7][8] In particular, captive animals commonly suffer from gastrointestinal (GI) pathology, [9][10][11] indicating that factors such as stress, and diet changes associated with captive management can result in changes to the GI microenvironment which compromise animal health. Horses constitute a prime example of a species which suffers from a high incidence of (often life-threatening) GI disease in captivity [12][13][14] ; prevalence of analogous diseases in wild populations are unknown due to lack of surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Domestication is associated with changes to an animal's natural environment, diet, breeding and behaviour, 1–4 often with a negative impact on animal health 5–8 . In particular, captive animals commonly suffer from gastrointestinal (GI) pathology, 9–11 indicating that factors such as stress, and diet changes associated with captive management can result in changes to the GI microenvironment which compromise animal health.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have been domesticating animals on this planet for thousands of years, with the rst cases in dogs estimated to be around 16,000 years ago [1]. This process is associated with changes to an animal's natural environment, diet, breeding and behaviour [2,3,4,5], often with a negative impact on animal health [6,7,8,9]. In particular, domesticated and/or captive animals commonly suffer from gastrointestinal (GI) pathology [10,11,12], indicating that domestication can result in changes to the GI microenvironment which compromise animal health.…”
Section: Introductionmentioning
confidence: 99%